Penelitian Agama Menurut H. A. Mukti Ali dan Kontribusinya Terhadap Pendidikan Islam - Muhamad Rifa'i Subhi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2015)
It is undeniable that religion is something that is needed by humans. Where religion is used as a benchmark and guide for the survival of his life. Therefore, it is very necessary the implementation of religious research that can make a major contribution in understanding what religion really is. In Indonesia, religion research has begun to emerge, but the results do not contribute to understanding what religion is. This was revealed by H. A. Mukti Ali who explained that religious research so far had not used the right method in its implementation. So he formulated a method called the synthesis method in response to his anxiety about the shortcomings of religious research so far. Through this method, religious research developed by Mukti Ali can produce the latest research results related to understanding of religion, including Islam. Because what is obtained is not only doctrinal, but also scientific in studying matters of religion. Thus, religious research can contribute or contribute to various other scientific disciplines, such as social, cultural, political, economic, including can also make a major contribution to the development of the concept of Islamic education.